In-service and pre-service physics and chemistry teachers’ knowledge and perceptions about renewable energies education - Sidi Mohamed Tounkara (Indonesian Journal of Chemical Education, 2025)
With climate change education (CCE) not included in Malian official programs of general secondary schools and physics and chemistry teachers are left to integrate it into their respective lessons. A survey was conducted to assess in-service and pre-service physics and chemistry (PC) teachers’ (n = 82) knowledges and perceptions for through renewable energies (RE) education in Mali. At the in-service teacher’s level, 85% desired to integrate RE, contrary to explaining climate change causes and consequences, perhaps because integration of CCE requires a didactic transposition that involves two major constraints: the legitimization of knowledge and the gap with scholarly knowledge, with compliance with programs to be satisfied first. Pre-service (master’s degree in PC) teachers’ results showed the influence of the disciplinary approach, with small differences and a complementarity of REs knowledge advantages and disadvantages, implying that teachers can actively participate in curricular innovation through CCE integration.